Research Progress in Nano-Structured MnO2 as Electrode Materials for Supercapacitors: A Review - Liu, Ting-Ting; Shao, Guang-Jie; Ji, Ming-Tong; Ma, Zhi-Peng (Asian Journal of Chemistry, 2013)
Manganese dioxide has been considered to be promising electrode materials for supercapacitors in terms of its abundant storage, low cost and superior electrochemica1 performance. Synthetic methods of preparing nano-structured MnO2 were summarized systematically and the recent developments were reviewed. The methods involved hydrothermal synthesis, sol-gel, chemical co-precipitation, low-temperature solid-state synthesis, electro-deposition, microemulsion, pyrolysis and microwave synthesis. Moreover, the solutions to improve the specific capacitance, electric conductivity and stabilization by doping or composite with carbon materials, metals and conductive polymers were also discussed. Finally, it indicates in the article that composite MnO2 electrode materials will become the main trend in future researches.